1985
DOI: 10.3181/00379727-178-42018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Carbohydrates on Hepatic Enzymes of Copper-Deficient Rats

Abstract: The present study was undertaken to measure the activities of several hepatic enzymes of regulatory importance in the pathways of lipogenesis and gluconeogenesis in rats fed diets marginally deficient in copper (1.2 p g Cu/g of diet) and containing either fructose, glucose, or starch as the carbohydrate sources. Although all copperdeficient rats exhibited the characteristic signs of copper deficiency, they were more pronounced in rats fed the diet containing fructose. Except for the activity of phosphoenolpyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Analysis of hepatic enzymes involved in the lipid and carbohydrate metabolism also indicated that a diet deficient in copper had greatest metabolic effects in combination with fructose, less with glucose and least with starch (71). Glucose-6-phosphate dehydrogenase, malic enzyme, L-alpha-glycerophosphate dehydrogenase and fructose 1-6-diphosphatase were all unaffected by Cu deficiency, but their activities were enhanced most in combination with fructose, suggesting a complementary rather than direct role for fructose in exacerbating copper deficiency (71).…”
Section: Fructose Lipids and Copper Metabolismmentioning
confidence: 95%
“…Analysis of hepatic enzymes involved in the lipid and carbohydrate metabolism also indicated that a diet deficient in copper had greatest metabolic effects in combination with fructose, less with glucose and least with starch (71). Glucose-6-phosphate dehydrogenase, malic enzyme, L-alpha-glycerophosphate dehydrogenase and fructose 1-6-diphosphatase were all unaffected by Cu deficiency, but their activities were enhanced most in combination with fructose, suggesting a complementary rather than direct role for fructose in exacerbating copper deficiency (71).…”
Section: Fructose Lipids and Copper Metabolismmentioning
confidence: 95%
“…Since all the rats of the present study consumed fructose, it was not surprising to find that liver size was not affected by the different dietary proteins. It is suggested that metabolism of fructose, which occurs mainly in the liver [18,19] was not altered by the nature of dietary protein.…”
Section: Discussionmentioning
confidence: 97%
“…Increased insulin concentration when garlic was fed resulted in a stimulation of lipogenesis by extrahepatic tissues as reflected by the elevated epididymal fat pad weights in Cu-deficient rats fed fructose. Fatty liver is a consequence of fructose but not of glucose (from the digestion of starch) metabolism [9][10][11]. One of the causes of fatty liver in fructose feeding is increased availability of fatty acids in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike starch, fructose is very lipogenic and its consump tion results in a fatty liver [9][10][11]. Chronic lipid accumu lation causes the liver cells to become fibrotic, leading to cirrhosis and impaired liver functions.…”
Section: Introductionmentioning
confidence: 99%